Gene therapy for long-term restoration of circulating thymulin in thymectomized mice and rats - Reggiani, Paula Cecilia (2006)
Thymulin is a thymic peptide possessing hypophysiotropic activity and antiinflammatory effects in the brain. We constructed a synthetic DNA sequence encoding met-FTS, a biologically active analog of thymulin, and subsequently cloned it into different expression vectors. A sequence optimized for expression of met-FTS in rodents, 5′-ATGCAGGCCAAGTCGCAGGGGGGGTCGAACTAGTAG-3′, was cloned in the mammalian expression vectors pCDNA3.1(+) and phMGFP (which expresses the Monster Green Fluorescent Protein), thus obtaining pcDNA3.1-metFTS and p-metFTS-hMGFP, which express met-FTS and the fluorescent fusion protein metFTS-hMGFP, respectively. The synthetic sequence was also used to construct the adenoviral vector RAd-metFTS, which expresses met-FTS. Transfection of HEK293 and BHK cells with pcDNA3.1-metFTS (experimental groups) or pcDNA3.1 (control), led to high levels of thymulin bioactivity (>600 versus < 0.1 pg/ml in experimental and control supernatants, respectively). Transfection of HEK293 and BHK cells with pmetFTS-hMGFP revealed a cytoplasmic and nuclear distribution of the fluorescent fusion protein. A single intramuscular (i.m.) injection (107 plaque forming units (PFU)/mouse or 108/PFU/rat) of RAd-metFTS in thymectomized animals (nondetectable serum thymulin) restored serum thymulin levels for at least 110 and 130 days post-injection in mice and rats, respectively. We conclude that RAd-metFTS constitutes a suitable biotechnological tool for the implementation of thymulin gene therapy in animal models of chronic brain inflammation.